Talent management : a decade of developments - Collings, David G.; Vaiman, Vlad, 1971-; Scullion, Hugh (Talent management., 2022)
This book contains an Open Access chapter. Aimed at researchers, postgraduate students, and professionals in the field, Talent Management: A Decade of Developmentscharts the evolution of talent management, illustrating the progress, prospects, and challenges that have transpired over the last ten years.